Moving beyond one-size-fits-all approaches to injury prevention: Evaluating how tailored injury prevention programs are developed and implemented in academy soccer - O'Brien, J.; Santner, E.; Kröll, J. (Journal of Orthopaedic & Sports Physical Therapy, 2021)
Objective: To evaluate the real-world development and implementation of tailored injury prevention exercise programs (IPEPs) in academy soccer players. Design: A mixed-methods process evaluation employing the Consolidated Framework for Implementation Research. Methods: The participants were 38 players and staff members (eg, coaches, physical therapists) from 4 male teams in 1 European soccer academy. The content and nature of the 4 teams' IPEPs and the degree of implementation across 1 playing season were evaluated. Additionally, participants took part in semi-structured interviews and focus groups, focusing on the development of tailored IPEPs and implementation barriers and facilitators. Results: Teams employed multiple IPEPs, developed by the team physical therapists and strength and conditioning coaches. A range of sources, including scientific literature, guidelines, individual player screening data, and previous experience, influenced IPEP development. Across all teams, 76% of IPEP sessions were completed as originally planned and a further 11% were completed in modified form. The key barriers to implementation during the season were related to scheduling changes and managing player workload. Thematic coding of interviews and focus groups identified 25 IPEP implementation barriers (eg, time and scheduling, player workload) and 41 facilitators (eg, program adaptability, facilities and equipment). Conclusion: In a male soccer academy setting, physical therapists and strength and conditioning coaches played the key role in IPEP development. Teams employed a range of different, internally developed programs. The key implementation factors were related to time and scheduling and managing player workload.